Pathological changes in anabolic androgenic steroid users. (July 2015) - Lusetti, Monia; Licata, Manuela; Silingardi, Enrico; Reggiani Bonetti, Luca; Palmiere, Cristian
Abstract: Several classes of recreational and prescription drugs have additional effects on the heart and vasculature, which may significantly contribute to morbidity and mortality in chronic users. The study presented herein focuses on pathological changes involving the heart possibly due to anabolic androgenic steroid use. The role these hormones may play in their occurrence of sudden cardiac death is also investigated. 98 medico-legal cases including 6 anabolic androgenic steroid users were retrospectively reviewed. Autopsies, histology, immunohistochemistry, biochemistry and toxicology were performed in all cases. Pathological changes consisted of various degrees of interstitial and perivascular fibrosis as well as fibroadipous metaplasia and perineural fibrosis within the myocardium of the left ventricle. Within the limits of the small number of investigated cases, our results appear to confirm former observations on this topic and suggest anabolic androgenic steroid's potential causative role in the pathogenesis of sudden cardiac deaths in chronic users. Highlights: Anabolic androgenic steroid use is associated with cardiac side effects. Pathological cardiac alterations are not systematically observed. Acute myocardial infarction is the most common fatal event. Potentially arrhythmogenic morphologic changes must be investigated systematically.